PENGEMBANGAN E-MODUL BERBANTUAN HEYZINE PADA MATERI KINI AKU MENJADI LEBIH TERTIB - Andrea Tiara Puspa; Elly Sukmanasa; Rini Sri Indriani (STKIP Subang, 2024)
The research subjects were class IV students at the Katulampa 1 State Elementary School, Bogor City, consisting of 24 students. The research was conducted in the even semester of the 2023/2024 academic year. The method used in this research is the ADDIE method. This research aims to determine the feasibility of E-modules developed with the help of Heyzine as accompanying teaching materials in elementary schools. In this research, validation tests were carried out on experts, namely material experts, language experts and media experts. The data results from the final score of the material expert validation are 100%, which means the product is very suitable for implementation. The final score obtained from the language expert is 100%, which means the product is very suitable for implementation. Media experts received a final score of 98%. Meanwhile, the results of research on distributing questionnaires showed that student responses were 87.1% and teacher responses were 94%, meaning that the Heyzine-assisted E-module was very feasible or very good to use.